High-freezing-resistance concrete as well as preparation method and application thereof
By using high-freeze-resistant concrete prepared with raw materials such as sulfa aluminate cement, combined with the combination of modified cement and silica solution, the problem of mechanical properties of concrete due to freeze-thaw in severe cold areas was solved, and the effect of significantly improving the freeze-resistant performance was achieved.
Patent Information
- Application Number
- CN202311131386.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
In severe cold areas in western my country, the expansion and contraction stress of concrete caused by freeze-thawing phenomenon causes microcracks, which in turn affects the mechanical properties of concrete and leads to insufficient freezing resistance.
High-frost-resistant concrete made of sulfaluminate cement, fly ash, river sand, recycled aggregate and silica is used to improve the frost-resistant properties of the concrete by combining modified cement and silica solution.
The high-freeze-resistant concrete reached 45.12MPa in compressive strength in 28 days, and its strength decreased by only 19.57% after 100 freeze-thaw cycles, significantly improving the freeze-resistant properties of the concrete.
Smart Images

Figure BDA0004430295190000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete materials, and in particular to a high frost resistance concrete and a preparation method and application thereof. Background Art
[0002] The cold regions in western my country are at high altitudes, with long hours of ultraviolet radiation and large seasonal temperature differences and morning and evening temperature differences, which lead to freezing and thawing of capillary water in concrete, causing uneven expansion and contraction stresses between the components in concrete, leading to a gradual increase in microcracks in concrete, which in severe cases cause cracking of concrete and a decrease in concrete mechanical properties. Therefore, improving the frost resistance of concrete is crucial for buildings in the cold regions in western my country. Crushing and reusing discarded concrete can not only reduce the consumption of natural gravel, but also effectively solve the construction waste generated with urbanization and achieve coordinated and green development. Summary of the invention
[0003] The purpose of the present invention is to provide a high frost resistance concrete and a preparation method and application thereof.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a high frost resistance concrete, which is prepared from the following raw materials in parts by weight: 250-350 parts of sulphoaluminate cement, 50-100 parts of fly ash, 650-750 parts of river sand, 1100-1250 parts of recycled aggregate, 7-15 parts of silicon dioxide, and 200-300 parts of water.
[0006] Preferably, the particle size of the silicon dioxide is 15 to 25 nm.
[0007] Preferably, the particle size of the recycled aggregate is 5 to 10 mm.
[0008] Preferably, the sulphoaluminate cement is prepared from the following raw materials in parts by weight:
[0009] 20-50 parts of coal gangue, 220-280 parts of carbide slag, and 5-20 parts of desulfurized lime paste.
[0010] Preferably, the method for preparing sulphoaluminate cement comprises the following steps:
[0011] The sulphoaluminate cement is obtained by mixing coal gangue and carbide slag, calcining them and then mixing them with desulfurized lime paste.
[0012] Preferably, the calcination temperature is 1250-1400° C., and the calcination time is 20-60 min.
[0013] The present invention also provides a method for preparing the high frost resistance concrete, comprising the following steps:
[0014] (1) mixing sulphoaluminate cement and fly ash to obtain modified cement;
[0015] (2) mixing silicon dioxide with water to obtain a silicon dioxide solution;
[0016] (3) dry-mixing the modified cement, river sand and recycled aggregate, adding the silicon dioxide solution and continuing to stir, and then sequentially performing molding and curing to obtain the high frost resistance concrete.
[0017] The invention also provides application of the high frost resistance concrete in building materials.
[0018] The present invention has the following beneficial effects:
[0019] The high frost resistance concrete provided by the present invention is prepared from the following raw materials in mass fractions: 250-350 parts of sulphoaluminate cement, 50-100 parts of fly ash, 650-750 parts of river sand, 1100-1250 parts of recycled aggregate, 7-15 parts of silicon dioxide, and 200-300 parts of water. The sulphoaluminate cement raw materials used in the present invention are coal gangue, carbide slag and desulfurized gypsum. Compared with high-emission and high-consumption silicate cement, it has the characteristics of lower carbon dioxide emissions, low cost, high early strength, etc., which can improve the utilization rate of industrial solid waste and reduce its pollution to the environment.
[0020] The present invention also provides a method for preparing high frost resistance concrete, comprising the following steps: (1) mixing sulphoaluminate cement and fly ash to obtain modified cement; (2) mixing silicon dioxide with water to obtain a silicon dioxide solution; (3) dry-mixing the modified cement, river sand, and recycled aggregate, adding the silicon dioxide solution and continuing to stir, and then sequentially forming and curing to obtain the high frost resistance concrete. Silicon dioxide can react quickly with calcium hydroxide produced by hydration of modified cement to form hydrated calcium silicate, and unreacted silicon dioxide can also play a role in filling micropores, thereby improving the frost resistance of concrete; at the same time, the selected silicon dioxide with high water absorption can reduce the fluidity of concrete, and the co-addition of fly ash can improve the workability of concrete; silicon dioxide improves the early strength of concrete, and fly ash improves the later strength of concrete.
[0021] The high frost resistance concrete provided by the present invention has a 28d compressive strength of 45.12 MPa, which has excellent compressive strength. After 100 freeze-thaw cycles, the strength still reaches 36.29 MPa, which only decreases by 19.57%, and has excellent frost resistance. DETAILED DESCRIPTION
[0022] The invention provides a high frost resistance concrete, which is prepared from the following raw materials in parts by weight: 250-350 parts of sulphoaluminate cement, 50-100 parts of fly ash, 650-750 parts of river sand, 1100-1250 parts of recycled aggregate, 7-15 parts of silicon dioxide, and 200-300 parts of water.
[0023] In the present invention, the mass fraction of the sulphoaluminate cement is preferably 260-340 parts, more preferably 280-320 parts, and more preferably 295-305 parts; the mass fraction of the fly ash is preferably 70-80 parts, more preferably 72-78 parts, and more preferably 74-76 parts; the mass fraction of the river sand is preferably 670-730 parts, more preferably 690-710 parts, and more preferably 695-705 parts; the mass fraction of the recycled aggregate is preferably 1150-1200 parts, more preferably 1160-1190 parts, and more preferably 1170-1180 parts; the mass fraction of the silicon dioxide is preferably 8-14 parts, more preferably 9-13 parts, and more preferably 10-12 parts; the mass fraction of the water is preferably 220-280 parts, more preferably 230-270 parts, and more preferably 240-260 parts.
[0024] In the present invention, the silica is preferably hydrophilic silica, and the particle size of the silica is preferably 15 to 25 nm, more preferably 17 to 23 nm, and even more preferably 19 to 21 nm.
[0025] In the present invention, the recycled aggregate is taken from conventional recycled demolition aggregate produced by Inner Mongolia Luya Resource Recycling Co., Ltd., with the product number LY-GL-Z-0-5-C-DB / T1148.
[0026] In the present invention, the particle size of the recycled aggregate is preferably 5 to 10 mm, more preferably 7 to 8 mm, and even more preferably 7.4 to 7.6 mm.
[0027] In the present invention, the mud content of the river sand is preferably ≤2%, further preferably ≤1.5%, and more preferably ≤1.0%. The particle size of the river sand is preferably 0.25-0.5 mm, further preferably 0.3-0.45 mm, and more preferably 0.35-0.40 mm.
[0028] In the present invention, the sulphoaluminate cement is prepared from the following raw materials in parts by weight:
[0029] 20-50 parts of coal gangue, 220-280 parts of carbide slag, and 5-20 parts of desulfurized lime paste.
[0030] In the present invention, the mass fraction of the coal gangue is preferably 25 to 45 parts, more preferably 30 to 40 parts, and more preferably 32 to 38 parts; the mass fraction of the carbide slag is preferably 230 to 270 parts, more preferably 240 to 260 parts, and more preferably 245 to 255 parts; the mass fraction of the desulfurization lime paste is preferably 8 to 17 parts, more preferably 10 to 15 parts, and more preferably 12 to 13 parts.
[0031] In the present invention, the preparation method of sulphoaluminate cement comprises the following steps:
[0032] The sulphoaluminate cement is obtained by mixing coal gangue and carbide slag, calcining them and then mixing them with desulfurized lime paste.
[0033] In the present invention, the coal gangue and carbide slag are firstly ground and sieved and then mixed and calcined.
[0034] In the present invention, the grinding rate is preferably 80-100 r / min, more preferably 85-95 r / min, and more preferably 88-92 r / min; the sieving mesh size is preferably 150-250 mesh, more preferably 180-220 mesh, and more preferably 190-210 mesh.
[0035] In the present invention, the calcination temperature is preferably 1250-1400°C, more preferably 1300-1350°C, more preferably 1320-1330°C, and the calcination time is preferably 20-60 min, more preferably 30-50 min, more preferably 35-45 min.
[0036] In the present invention, the sulphoaluminate cement is obtained by mixing and calcining the mixture of coal gangue and carbide slag and desulfurized lime paste, grinding the mixture and sieving the mixture.
[0037] In the present invention, the grinding rate is preferably 80-100 r / min, more preferably 85-95 r / min, and more preferably 88-92 r / min; the sieving mesh size is preferably 150-250 mesh, more preferably 180-220 mesh, and more preferably 190-210 mesh.
[0038] The present invention also provides a method for preparing the high frost resistance concrete, comprising the following steps:
[0039] (1) mixing sulphoaluminate cement and fly ash to obtain modified cement;
[0040] (2) mixing silicon dioxide with water to obtain a silicon dioxide solution;
[0041] (3) Dry mix the modified cement, river sand and recycled aggregate, then add the silica solution and continue stirring ,Then, the high frost resistance concrete is obtained by sequentially performing molding and curing.
[0042] In the present invention, the mixing rate in step (1) is preferably 10 to 30 r / min, more preferably 15 to 25 r / min, more preferably 18 to 22 r / min, and the mixing time is preferably 5 to 30 min, more preferably 10 to 25 min, more preferably 15 to 20 min.
[0043] In the present invention, the stirring rate of the mixing in step (2) is preferably 35 to 55 r / min, more preferably 40 to 50 r / min, more preferably 42 to 48 r / min, and the mixing time is preferably 5 to 20 min, more preferably 10 to 15 min, more preferably 12 to 13 min.
[0044] In the present invention, the dry mixing rate in step (3) is preferably 10 to 30 r / min, more preferably 15 to 25 r / min, more preferably 18 to 22 r / min, the dry mixing time is preferably 5 to 25 min, more preferably 10 to 20 min, more preferably 12 to 18 min, the stirring rate is preferably 10 to 30 r / min, more preferably 15 to 25 r / min, more preferably 18 to 22 r / min, the stirring time is preferably 5 to 25 min, more preferably 10 to 20 min, more preferably 12 to 18 min. The preferred curing time is 15 to 30 days, more preferably 20 to 25 days, more preferably 22 to 23 days, and the preferred curing humidity is 92 to 97%, more preferably 93 to 96%, more preferably 94 to 95%.
[0045] The invention also provides application of the high frost resistance concrete in building materials.
[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0047] Example 1
[0048] The silicon dioxide is hydrophilic silicon dioxide with a particle size of 15 nm; the recycled aggregate is selected from Inner Mongolia Luya Resource Recycling Co., Ltd., the product number is LY-GL-Z-0-5-C-DB / T1148, and the particle size is 5 mm; the mud content of the river sand is 2%, and the particle size is 0.25 mm.
[0049] Take 31 parts of coal gangue and 233 parts of carbide slag, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve. Then calcine them at 1340℃ for 40min, add 11 parts of desulfurized lime paste, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve to obtain sulphoaluminate cement.
[0050] Take 275 parts of sulphoaluminate cement and 68.7 parts of fly ash and mix them at a rate of 20 r / min for 20 minutes to obtain modified cement;
[0051] 10.3 parts of silicon dioxide and 232 parts of water were mixed at a rate of 45 r / min for 15 min to obtain a silicon dioxide aqueous solution;
[0052] The modified cement was dry-mixed with 687 parts of river sand and 1182 parts of recycled aggregate at a rate of 10 r / min for 5 minutes, and then the silica solution was added and stirred for 10 minutes. The mixture was vibrated on a vibration table and then cured at 20°C and 95% humidity for 28 days to obtain high frost resistance concrete.
[0053] Example 2
[0054] The silicon dioxide is hydrophilic silicon dioxide with a particle size of 25 nm; the recycled aggregate is selected from Inner Mongolia Luya Resource Recycling Co., Ltd., the product number is LY-GL-Z-0-5-C-DB / T1148, and the particle size is 10 mm; the mud content of the river sand is 1.8%, and the particle size is 0.5 mm.
[0055] Take 20 parts of coal gangue and 220 parts of carbide slag, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve. Then calcine them at 1250℃ for 20min, add 5 parts of desulfurized lime paste, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve to obtain sulphoaluminate cement.
[0056] Take 300 parts of sulphoaluminate cement and 50 parts of fly ash and mix them at a rate of 20 r / min for 15 minutes to obtain modified cement;
[0057] 7 parts of silicon dioxide and 200 parts of water were mixed at a rate of 45 r / min for 15 min to obtain a silicon dioxide aqueous solution;
[0058] The modified cement was dry-mixed with 650 parts of river sand and 1100 parts of recycled aggregate at a rate of 15 r / min for 5 minutes, and then the silica solution was added and stirred for 10 minutes. The mixture was vibrated on a vibration table and then cured at 20°C and 95% humidity for 28 days to obtain high frost resistance concrete.
[0059] Example 3
[0060] The silicon dioxide is hydrophilic silicon dioxide with a particle size of 20 nm; the recycled aggregate is selected from Inner Mongolia Luya Resource Recycling Co., Ltd., the product number is LY-GL-Z-0-5-C-DB / T1148, and the particle size is 8 mm; the mud content of the river sand is 1.5%, and the particle size is 0.4 mm.
[0061] Take 50 parts of coal gangue and 280 parts of carbide slag, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve. Then calcine them at 1400℃ for 60min, add 20 parts of desulfurized lime paste, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve to obtain sulphoaluminate cement.
[0062] Take 350 parts of sulphoaluminate cement and 100 parts of fly ash and mix them at a rate of 20 r / min for 20 minutes to obtain modified cement;
[0063] Take 15 parts of silicon dioxide and 300 parts of water and mix them at a rate of 45 r / min for 15 minutes to obtain a silicon dioxide aqueous solution;
[0064] The modified cement was dry-mixed with 750 parts of river sand and 1250 parts of recycled aggregate at a rate of 15 r / min for 5 minutes, and then the silica solution was added and stirred for 10 minutes. The mixture was vibrated on a vibration table and then cured at 20°C and 95% humidity for 28 days to obtain high frost resistance concrete.
[0065] Example 4
[0066] The silicon dioxide is hydrophilic silicon dioxide with a particle size of 23 nm; the recycled aggregate is selected from Inner Mongolia Luya Resource Recycling Co., Ltd., the product number is LY-GL-Z-0-5-C-DB / T1148, and the particle size is 6 mm; the mud content of the river sand is 1.5%, and the particle size is 0.3 mm.
[0067] Take 45 parts of coal gangue and 275 parts of carbide slag, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve. Then calcine them at 1380℃ for 45min, add 20 parts of desulfurized lime paste, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve to obtain sulphoaluminate cement.
[0068] Take 450 parts of sulphoaluminate cement and 80 parts of fly ash and mix them at a rate of 20 r / min for 25 minutes to obtain modified cement;
[0069] Take 10 parts of silicon dioxide and 280 parts of water and mix them at a rate of 45 r / min for 15 minutes to obtain a silicon dioxide aqueous solution;
[0070] The modified cement was dry-mixed with 700 parts of river sand and 1150 parts of recycled aggregate at a rate of 15 r / min for 5 minutes, and then the silica solution was added and stirred for 10 minutes. The mixture was vibrated on a vibration table and then cured at 20°C and 95% humidity for 28 days to obtain high frost resistance concrete.
[0071] Comparative Example 1
[0072] Take 40 parts of coal gangue and 300 parts of carbide slag, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve. Then calcine them at 1340℃ for 40min, add 14 parts of desulfurized lime paste, grind them at a speed of 90r / min, and then pass through a 200-mesh square hole sieve to obtain sulphoaluminate cement.
[0073] The above sulphoaluminate cement, 687 parts of river sand, 1182 parts of recycled aggregate and 232 parts of water were stirred at a rate of 15 r / min for 10 minutes and then vibrated on a vibration table to form the concrete, which was then cured at a temperature of 20° C. and a humidity of 95% for 28 days to obtain concrete.
[0074] The products prepared in Example 1 and Comparative Example 1 were tested for compressive strength after 7, 14, 28 days and 50 and 100 freeze-thaw cycles according to the "Standard Test Method for Long-term Performance and Durability of Ordinary Concrete" and the "Standard Test Method for Physical and Mechanical Properties of Concrete". The specific results are shown in Table 1:
[0075] Table 1 Compression test results of high frost resistance concrete obtained in Example 1 and Comparative Example 1
[0076]
[0077] It can be seen from Table 1 that the strength of the high-resistance concrete obtained by the present invention reaches 28.63 MPa at 7 days, and the strength at 28 days reaches 45.12 MPa, which is far higher than that of Comparative Example 1; with the increase of the number of freeze-thaw cycles, the compressive strength of the specimens gradually decreases, but the compressive strength of the embodiment is still greater than that of the comparative example.
[0078] It can be seen from the above embodiments that the present invention provides a high frost resistance concrete, which is prepared by the following raw materials in mass fractions: 250-350 parts of sulphoaluminate cement, 50-100 parts of fly ash, 650-750 parts of river sand, 1100-1250 parts of recycled aggregate, 7-15 parts of silicon dioxide, and 200-300 parts of water. The sulphoaluminate cement raw materials used in the present invention are coal gangue, carbide slag and desulfurized gypsum. Compared with high-emission and high-consumption silicate cement, it has the characteristics of lower carbon dioxide emissions, low cost, high early strength, etc., which can improve the utilization rate of industrial solid waste and reduce its pollution to the environment. According to the test, the strength of the high frost resistance concrete provided by the present invention reached 28.63MPa at 7d, and 45.12MPa at 28d. After 100 cycles of freezing and thawing, the compressive strength still reached 36.29MPa, with excellent compressive strength and frost resistance.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high frost resistance concrete, characterized in that: Prepared from the following raw materials in parts by weight: 250-350 parts of sulphoaluminate cement, 50-100 parts of fly ash, 650-750 parts of river sand, 1100-1250 parts of recycled aggregate, 7-15 parts of silicon dioxide, and 200-300 parts of water.
2. The high frost resistance concrete according to claim 1, characterized in that: The particle size of the silicon dioxide is 15 to 25 nm.
3. The high frost resistance concrete according to claim 1 or 2, characterized in that: The particle size of the recycled aggregate is 5 to 10 mm.
4. The high frost resistance concrete according to claim 3, characterized in that: The sulphoaluminate cement is prepared from the following raw materials in parts by weight: 20-50 parts of coal gangue, 220-280 parts of carbide slag, and 5-20 parts of desulfurized lime paste.
5. The high frost resistance concrete according to claim 4, characterized in that: The preparation method of the sulphoaluminate cement comprises the following steps: The sulphoaluminate cement is obtained by mixing coal gangue and carbide slag, calcining them and then mixing them with desulphurized lime paste.
6. The high frost resistance concrete according to claim 5, characterized in that: The calcination temperature is 1250-1400° C., and the calcination time is 20-60 minutes.
7. The method for preparing the high frost resistance concrete according to any one of claims 1 to 6, characterized in that: It includes the following steps: (1) mixing sulphoaluminate cement and fly ash to obtain modified cement; (2) mixing silicon dioxide with water to obtain a silicon dioxide solution; (3) dry-mixing the modified cement, river sand and recycled aggregate, adding the silicon dioxide solution and continuing to stir, and then sequentially performing molding and curing to obtain the high frost resistance concrete.
8. Use of the high frost resistance concrete according to any one of claims 1 to 6 in building materials.